2017
DOI: 10.3892/ol.2017.7015
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 expression is associated with the occurrence and development of esophageal squamous cell carcinoma

Abstract: Abstract. Beclin 1 has a central role in the regulation of autophagy, differentiation, apoptosis resistance, tumorigenesis and cancer progression. The role of Beclin 1 in the development of esophageal squamous cell carcinoma (ESCC) and its subsequent progression is not fully characterized. In the present study, the role of Beclin 1 and autophagy in ESCC was evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…We found that the expression of Beclin-1 significantly affected the number of invasive cells in EC9706 only when Bcl-2 was highly expressed. One of our previous study [ 20 ] and another study by Farkas et al [ 21 ] showed that Beclin-1 and Bcl-2 could be prognositc predictive marks in ESCC respectively. Our present study indicate that increased expression of Beclin-1 protein may reduce the invasiveness of EC9706 cells only in combination with high Bcl-2 expression levels.…”
Section: Discussionmentioning
confidence: 96%
“…We found that the expression of Beclin-1 significantly affected the number of invasive cells in EC9706 only when Bcl-2 was highly expressed. One of our previous study [ 20 ] and another study by Farkas et al [ 21 ] showed that Beclin-1 and Bcl-2 could be prognositc predictive marks in ESCC respectively. Our present study indicate that increased expression of Beclin-1 protein may reduce the invasiveness of EC9706 cells only in combination with high Bcl-2 expression levels.…”
Section: Discussionmentioning
confidence: 96%
“…Co-occurrence of ATG7 deletions with amplification in NFE2L2 [4], encoding the antioxidant mediator NRF2, support ATG7 as a critical mediator of oxidative stress [1517]. Decreased and/or lost expression of BECLIN 1, an effector of AV nucleation, was also reported in ESCC tumors [18,19]. Complementary BECLIN 1 knockdown and overexpression experiments further revealed a respective increase and decrease in invasion of EC9706 ESCC cells, supporting a potential functional role for BECLIN 1 downregulation in ESCC progression [19].…”
Section: Expression Of Atg Genes and Proteins Is Altered In Esccmentioning
confidence: 99%
“…Autophagy inhibition was achieved by the transfection of cells with Becn1 small interfering (si)RNA; knockdown in SH-SY5Y cells decreased LC3-II content, thereby suppressing cell viability (58). Reduction of Beclin-1 by siRNA resulted in defective autophagy and decreased the number of AVOs in human glioblastoma U87 and esophageal squamous cell carcinoma EC9706 cells (63,64).…”
Section: Discussionmentioning
confidence: 99%